PUBLIC INVESTMENT IN A HIERARCHICAL EDUCATIONAL SYSTEM WITH CAPITAL–SKILL COMPLEMENTARITY. (18th October 2016) - Sarid, Assaf
Abstract : In this study I bring together two different literatures: the hierarchical education literature and the skill-biased growth literature. In an overlapping-generations model I introduce capital–skill complementarity into a hierarchical education system. I obtain results that differ qualitatively from previous studies, among which are the following: (i) At earlier stages of development, basically educated labor contributes to growth more than highly educated labor. The opposite occurs at later stages. (ii) Even when all individuals acquire higher education, a growth-enhancing policy subsidizes higher education. (iii) In a growth-enhancing policy, the share of public resources allocated to basic education declines as the economy grows. (iv) The enrollment rate evolves in an S-shaped pattern, as occurred in several OECD countries.